The Five Bhāvanakrama of Kamalaśīla and Vimalamitra : a collection of texts on the nature and practice of Buddhist contemplative realisation - Kamalaśīla, fl. 713-763; Vimalamitra, 8th cent (Gonpo Tsheten, 1977)
On the nature of Buddhist meditation and practice.